2019
DOI: 10.1002/acn3.50965
|View full text |Cite
|
Sign up to set email alerts
|

Transmembrane protease serine 5: a novel Schwann cell plasma marker for CMT1A

Abstract: ObjectiveDevelopment of biomarkers for Charcot‐Marie‐Tooth (CMT) disease is critical for implementing effective clinical trials. The most common form of CMT, type 1A, is caused by a genomic duplication surrounding the PMP22 gene. A recent report (Neurology 2018;90:e518–3524) showed elevation of neurofilament light (NfL) in plasma of CMT1A disease patients, which correlated with disease severity. However, no plasma/serum biomarker has been identified that is specific to Schwann cells, the most directly affected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(53 citation statements)
references
References 47 publications
0
51
1
1
Order By: Relevance
“…The axonal injury protein NfL has shown to be a potent serum biomarker in a number of neurological conditions (17), including ALS, CMT and SMA (18,19,20). However, in our measurements, the level of serum NfL was not significantly different in SMAJ patient samples (median 14.9 pg/ml) compared to controls (13.6 pg/ml) (Fig 1A).…”
Section: Resultsmentioning
confidence: 99%
“…The axonal injury protein NfL has shown to be a potent serum biomarker in a number of neurological conditions (17), including ALS, CMT and SMA (18,19,20). However, in our measurements, the level of serum NfL was not significantly different in SMAJ patient samples (median 14.9 pg/ml) compared to controls (13.6 pg/ml) (Fig 1A).…”
Section: Resultsmentioning
confidence: 99%
“…The correlative module could be grouped into five modules: the first module was mainly dominated by the biological processes related to the activity of the nervous system. Among these biological processes, axon ensheathment, myelination, peripheral nervous system development, and Schwann cell development have been well studied, involving the axons, myelin sheaths, or peripheral nervous system as well as the progress of Charcot-Marie-Tooth Disease [ 46 49 ]. The second module and the third module can be defined together as a transmission function-related biological process.…”
Section: Discussionmentioning
confidence: 99%
“…56 Another biomarker found to be elevated in CMT1A plasma sample is the neurofilament L protein that was correlated with the increase in the severity of CMTN scores in CMT1A patient. 57 A new specific biomarker for CMT1A was recently identified by Wang et al 58 The transmembrane protease serine 5 (TMPRSS5) protein was found to be elevated by around 2-folds in the plasma of CMT1A patients. 58 Moreover, several genes were found to be alteredin PMP22 transgenic mouse model (TgN248) that could be targeted for future therapy.…”
Section: Peripheral Myelin Protein: Physiological Role and Disordersmentioning
confidence: 99%
“…57 A new specific biomarker for CMT1A was recently identified by Wang et al 58 The transmembrane protease serine 5 (TMPRSS5) protein was found to be elevated by around 2-folds in the plasma of CMT1A patients. 58 Moreover, several genes were found to be alteredin PMP22 transgenic mouse model (TgN248) that could be targeted for future therapy. 59 Since the discovery of the main cause of CMT1A, that is PMP22 overexpression resulting from the trisomy of PMP22 gene in addition to neurological dysfunctions which are due to loss of large-caliber motor and sensory axons, several animal models and therapeutic strategies were developed.…”
Section: Peripheral Myelin Protein: Physiological Role and Disordersmentioning
confidence: 99%